THE ORBIT OF THE STAR S2 ≡ S0-2 IN THE CENTER OF THE GALAXY - Denissyuk, E.K.; Serebryanskiy, A.V. (Academic Scientific Journal of Computer Science, 2020)
The study of the center of the Galaxy in the IR wavelengths, using the largest telescopes, aloud us to obtain data on coordinates and radial velocities for several tens of stars located in the immediate vicinity of the supermassive central body of the Galaxy, hereinafter (CB) Such data for S2≡S0-2 –one of the brightest and closest to the center stars, were used by us to determine the parameters of its orbit. The method we proposed was used to calculate the positions and velocities of a star in its orbit with the parameters at which the calculated coordinates and velocities best coincided with those observed. In order to estimate the errors of parameters, the Monte Carlo method was used. In this case, it was assumed that there was diffuse matter near the center of the Galaxy. An estimate of the average value of its density (5.2 ± 1.5) × 106 M⊙ / ps3 is obtained, which is comparable with the density of typical nebulae. The presence of such matter leads to the rotation of the orbit around the center of gravity. A full revolution of the orbit requires about 7760 years. In addition to the direct parameters of the star’s orbit the parameters of the CB itself were found. The mass of the CB of the Galaxy turned out to be (4034 ± 13) × 103M⊙, and its distance from the Sun is 8333.0 ± 7.0 ps.